Implementation of Digit Alization of Tax Payment Services Using the Linkaja Application to Increase Pad in Kendari City - Hasnita, Nita; Supriyadi, Supriyadi; Kolewora, Riez Kifli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to find out how the application of digitizing tax payment services using the LinkAja application can increase PAD in Kendari City. This objective is based on the urgency of the problem, namely (1) the payment system using the LinkAja application is not optimal and evenly distributed to all types of regional taxes and levies in Kendari City; (2) The implementation of the payment system for regional revenue by the community is still mostly done in cash, and (3) the implementation of digitalization has not been supported by the availability of regional regulations. This study was structured using a descriptive qualitative approach by conducting interviews, observations, and documentation studies of informants. The data analysis technique uses data reduction, data presentation, data verification, and drawing conclusions. Based on the results of the study, it shows that the utilization of the LinkAja application has been running since November 2021 but has not been optimal. Although compared to 2021, which only lasted 2 months, but has reached 2 digits, UN revenue in 2022 has increased but the cash flow is relatively low. This study recommends that the Kendari City Government maximize all existing digitization system services. This study provides an overview and understanding of the application of digitizing tax payment services using the LinkAja application that can contribute to increasing PAD in Kendari City.